Pengaruh Brand Image, Country Of Origin, Dan Harga Terhadap Minat Beli Handphone Xiaomi (Studi Kasus Pada Masyarakat Kabupaten Bengkulu Selatan) - Galian Ramdani Harun; Sri Handayani; Kamelia Astuty (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to examine the influence of brand image, country of origin, and price on the purchase intention of Xiaomi smartphones among consumers in Bengkulu Selatan Regency, Indonesia. The increasing competitiveness of the smartphone market highlights the importance of understanding how consumer perceptions shape purchase intentions, particularly for brands competing in the mid-to-low price segment such as Xiaomi. Employing a quantitative approach with a survey method, this research involved 95 respondents selected through purposive sampling, with data collected using a structured questionnaire and analyzed through multiple linear regression to assess both partial and simultaneous effects of the independent variables on purchase intention. The regression analysis produced the equation Y = 1.773 + 0.388X₁ + 0.352X₂ + 0.300X₃ + e, revealing that brand image (X1) had a positive and significant effect on purchase intention (Y), with a significance value of 0.000 < 0.05 and a t-value greater than the t-table (5.147 > 1.661). Similarly, country of origin (X2) showed a positive and significant effect with a significance value of 0.000 < 0.05 and t-value > t-table (4.488 > 1.661), while price (X3) also demonstrated a positive and significant influence with a significance value of 0.000 < 0.05 and t-value > t-table (4.236 > 1.661). The simultaneous test indicated a significance value of F = 0.000 < 0.05 and F-value > F-table (86.411 > 2.70), confirming that brand image, country of origin, and price collectively have a significant impact on consumers’ purchase intention toward Xiaomi smartphones.